Apresentação - Ulisses Frade dos Reis, Cecília; Luiz Correa, Vinícius; Camargo Miranda, Antônio César; Barossi, Giulia Maria (Sociologias Plurais, 2024)
Apresentação do volume 10, número 2 - Revista Sociologias Plurais.